Partisipasi Masyarakat Dalam Menjaga Kebersihan Pada Kegiatan Car Free Day (CFD) Kota Padang - Alberto Prima Putra; Deded Chandra (Geosfera: Jurnal Penelitian Geografi, 2025)
This research aims to: 1) identify the forms of community participation in maintaining cleanliness during Car Free Day (CFD) activities in Padang City, 2) analyze the supporting and inhibiting factors of community participation in maintaining cleanliness during CFD activities in Padang City, and 3) provide recommendations and strategies for CFD cleanliness management based on the level of community participation. This study employs a mixed-methods approach, utilizing descriptive qualitative and quantitative methods through observation, questionnaires, and interviews. The results indicate that community participation is categorized as fairly good, characterized by individual awareness to dispose of waste in the provided bins. However, collective participation, such as mutual cooperation, is still low. Supporting factors include high public awareness and knowledge of the importance of comfort when exercising and the initiative of traders in managing waste, while inhibiting factors include the behaviour of visitors who litter, lack of facilities, minimal socialisation, and limited supervision. This study recommends improving sanitation facilities, environmental campaigns, community empowerment, cross-sector coordination, the implementation of sanctions and rewards, and the use of digital innovations to strengthen community participation. These strategies are expected to create a cleaner and more sustainable CFD in Padang City.